صناديق التمويل العربية ودورها في دعم عملية التنمية في الدول العربية - أبا زيد ثناء; قابقلي ابتهال أحمد (Latakia University Journal - Economic and Legal Sciences Series, 2019)
لقد احتلت التنمية الاقتصادية أهمية بالغة وأصبحت هدفاً رئيسياً لمعظم الدول، خاصة بعد أن نالت استقلالها السياسي, وسعت الدول العربية كغيرها من الدول من أجل تحقيق تنميتها الاقتصادية والاجتماعية، ولكنها كانت تعاني من مشكلة جوهرية، وهي ضعف الموارد المحلية اللازمة لعملية التنمية، مما اضطر تلك الدول إلى اللجوء إلى الاقتراض الخارجي، خاصة من مؤسسات التمويل الدولية التي يأتي في مقدمتها البنك الدولي ولكن شروط تلك المؤسسات لم تكن مواتية للدول العربية, وكانت صناديق التمويل العربية بديل مهمّاً لتلك المؤسسات, وذلك لأن العون المقدم من هذه الصناديق يتمتع بمزايا استثنائية لكونه يقدم من دول نامية إلى دول نامية أخرى ولهذا فإن شروطه منزهة عن أي استغلال وغير مرتبطة بأي شروط تجارية ولا يشكل أي تهديد للدول المتلقية , إضافة إلى أن قروضها تتميز بشروط مالية وقانونية ميسرة أكثر يسراً من مصادر التمويل الدولية، ويتمثل هذا اليسر في انخفاض سعر الفائدة وطول فترتي السماح والسداد. Economic development has occupied great importance and it has become a main goal for most countries especially when they gained their independence. Arab states, like any other countries, have been working to achieve their economic and social development. However, they have suffered from a major problem which is lack of local resources required for the process of development. This problem has obliged these countries to resort to foreign borrowing especially from international funds, the first of which is the World Bank (WB). Their terms were not suitable for the Arab states, therefore, Arab Funds (AFs) were important alternatives to these institutions because this assistance offered by these funds enjoys exceptional privileges, being offered by developing countries to other developing countries. Therefore, their terms are exploitation-free and are not connected with any commercial terms, and they do not from any threat to the receiving countries. Moreover, their loans are characterized with easier financial and legal terms than those offered by international funding sources. This easiness is represented in low interest rate and longer allowance and payment periods.